Seed delivery system in northeastern Democratic Republic of Congo: characteristics, stakeholders mapping and challenges towards building a well-functioning seed system under humanitarian and security crises - Jean M. Mondo; Adrien B. Ndeko; Rodrigue B. Ayagirwe; Henri M. Matiti; Chance Bahati; René M. Civava (International Journal of Agricultural Sustainability)
Quality seed is one of the most important farm inputs. The Ituri province, in northeastern Democratic Republic of Congo (DRC), faces enormous challenges in implementing a coherent formal seed sector, an essential gage for seed quality. This study aimed at diagnosing the Ituri seed value chain to propose improvements at all levels. Data collection was conducted using focus group discussions and direct interviews with key players at all levels, household surveys across the province, and a review of seed intervention programme reports, farm visit reports and other literature. Results showed that the seed system in the northeastern DRC is mainly informal due to several socioeconomic and technical factors. Less than a third of crops in the region had a formal seed delivery system. The cash flow in the seed sector was high owing to high seed demands from humanitarian organizations and farmer support structures, estimated at ∼1.5 million US$ in 2022 for the top three commercial seed commodities (common beans, maize and peanuts). However, the province seed production capacity through formal pathway is low (only ∼35 and 69% of the demands for common bean and maize, respectively, are covered by local productions), meaning that the seed demand is met either through importation or fraudulent conversion of farmer-saved seed. Due to lack of technical capacities, Ituri seed multipliers mainly produce open pollinated and synthetic varieties, while hybrids are imported from neighbouring countries. The lack of functional breeders in the provincial seed production chain, disproportionately low seed multipliers-to-distributors ratio, the weakness of the seed certification and regulation services, the border porosity, poor coordination among actors, and low awareness of farmers on seed qualities and advantages of using certified quality seed are the main structural and functional factors hindering the well-functioning of northeastern DRC seed system. This study provided an insight on the characteristics, stakeholders and challenges facing the seed sector in northeastern DRC and proposed an action plan for its improvement.